金庸武侠小说中的“面具”人物 ：以杨过、黄药师、程英为探讨中心 = The "Mask characters" in Jin Yong's Wuxia novels : focusing on Yang Guo, Huang Yaoshi and Cheng Ying - 方一然 Fang, Yiran (Nanyang Technological University, 2021)
金庸武侠世界中，有不少头戴“面具”的江湖人物。“面具”，本是晚清暨旧派武侠小说家笔下，侠客用以防身呵敌的江湖装备。及至金庸笔下，“面具”之重要性显然不再只是普通侠客的防身物件，而成为了某类人物的“专属标志”。在二十世纪新派武侠小说注重人物心理及人物性格刻画的基础上，笔者以为，“面具”正是金庸借以塑造笔下人物，并表现其情感、个性及相互关系的重要手段。 本文试图以杨过、黄药师、程英作为金庸笔下“面具”人物的代表，由“面具”作为切入点，分析金庸小说人物的形象及性格，并探讨金庸在为他们“绘面”时所流露出的对个人与社会、“正邪之辨”、爱情贞节观等问题的思考。本文也以“闲笔”对金庸小说中的“面具”书写定位，并观览其他文学与影视作品中的“面具”，探求其与金庸所绘“面具”间的承转关系。 Wearing a “Mask” in a life of wandering is the preference of many characters in Jin Yong’s Wuxia Novels. “Masks” were initially the equipment of Chinese swordsmen for self-defense and disguise in Late Qing and “Old School” Wuxia Novels. The importance of “masks” was then highlighted by Jin Yong in his Wuxia novels where the “masks” became the symbols of the characters mentioned above, instead of a kind of defensive equipment. Thus, the author believes that the “masks” was manipulated by Jin Yong to create his characters amid the proliferation of “New School” Wuxia Novels which focused on the portrayal of characters’ personalities. This paper chooses Yang Guo, Huang Yaoshi and Cheng Ying as the three representations of the “Mask Characters” in Jin Yong’s Wuxia Novels. Firstly, the paper analyzes the personalities and character images of the three characters with a focus on their “masks”. Then, the paper discusses some questions raised by Jin Yong as he created the “masks” of the characters. These questions include the relationship of the individual and society, the difference between the good and the evil, and the acceptance of chastity by traditional Chinese women. Finally, the paper examines Jin Yong’s writing of subplots with a focus on the “Masks”, and compares the “Masks” in Jin Yong’s novels with the “Masks” in other literature works, films and televisions, to discuss their similarities and differences.